The Role of Vitamins A and E Level in Chronic Suppurative Otitis Media with and without Cholesteatoma - Boesoirie SF; Hasansulama W; Lasminingrum L; Novianto AT; Gatera VA; Aroeman NA; Boesoirie TS (Journal of Multidisciplinary Healthcare, 2023)
Shinta Fitri Boesoirie,1 Wijana Hasansulama,1 Lina Lasminingrum,1 Arif Tria Novianto,1 Vesara Ardhe Gatera,2,3 Nur Akbar Aroeman,1 Thaufiq Siddiq Boesoirie1 1Department of Otorhinolaryngology-Head and Neck Surgery Faculty of Medicine Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 2Department of Pharmacy and Health Sciences, Universiti Kuala Lumpur – Royal College of Medicine Perak, Ipoh, Perak, Malaysia; 3Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Shinta Fitri Boesoirie, Department of Otorhinolaryngology-Head and Neck Surgery Faculty of Medicine Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, Tel +62 22 84288828, Email shinta.fitri.boesoirie@unpad.ac.idAim: High expression of lytic enzymes and cytokines is related to cell proliferation in Otitis Media Chronic Suppurative (CSOM) with cholesteatoma. In addition, the process of inflammation healing and maintenance of homeostatic conditions requires Reactive Oxygen Species (ROS), which can cause significant damage to cells. To address this issue, secondary antioxidants such as Vitamins A and E are used to inhibit and neutralize the occurrence of oxidation reactions. These vitamins complement each other, with vitamin A working effectively at low concentrations of oxygen, while vitamin E functions in the opposite manner.Purpose: This study aims to investigate the roles of vitamin A and E levels in CSOM patients with Cholesteatoma.Patients and Methods: The study was conducted between July and December 2020, and the method used was an analytical observational approach with a case–control design. The sample population comprised 60 CSOM patients divided into 2 groups. These included those with and without cholesteatoma.Results: The results showed that there was no significant difference between these two groups in terms of the impact of vitamin A and E levels (respectively, p = 0.626, p = 0.864).Conclusion: Considering these results, it was discovered that vitamins A and E levels do not influence the occurrence of CSOM with or without cholesteatoma.Keywords: antioxidants, cholesteatoma, CSOM, ROS, vitamin A, vitamin E